Intestinal morphology and growth performance of the Indonesian indigenous crossbred chickens supplemented with formic acid and Saccharomyces cerevisiae - Erya, S. N.; Wahyuni, H. I.; Yudiarti, T.; Widiastuti, E.; Sugiharto, S. (Diponegoro University, 2020)
The study investigated gut ecology and morphology of the Indonesian indigenous crossbred chickens (IICC) supplemented with the combination of formic acid and Saccharomyces cerevisiae. Two hundreds day-old IICC were distributed to T0 (control diet), T1 (T0 + 0.2% formic acid), T2 (T0 + 0.3% S. cerevisiae), T3 (T0 + 0.2% formic acid and 0.3% S. cerevisiae). Excreta was collected at week 8, while intestinal ecology and morphology were determined at week 9. In duodenum, T3 chicks showed higher and wider (P<0.05) villi. The T2 and T3 chicks showed deeper (P<0.05) crypt than that of T0. The jejunal villi was higher (P<0.05) in T3 than in T0. The T3 chicks had deeper (P<0.05) crypt compared to other groups. In ileum, the villi height was lowest (P<0.05) in T0. The crypt was deeper (P<0.05) in T3 than in other. Crude protein digestibility coefficient was highest (P<0.05), while fecal protein was loswest (P<0.05) in T1 than in other groups. Compared to T0, the treated IICC showed higher (P<0.05) weight gain and feed intake with T3 had the highest gain and intake but gain:feed rasio was the lowest (P>0.05). IIn conclusion, the inclusion of formic acid and S. cerevisiae in diets improved intestinal ecology and morphology. The IICC chickens fed with formic acid and S. cerevisiae exhibited improved growth performance and nutrient digestibility.